2013
DOI: 10.1002/tie.21568
|View full text |Cite
|
Sign up to set email alerts
|

How Do SMEs with Single and Multiple Owners Finance Their Operations Differently? Empirical Evidence from China

Abstract: We study the impact of firm‐level characteristics on the capital structures of private small and medium‐sized enterprises (SMEs) as well as the differences between the capital structures adopted by SMEs with single and multiple owners in China. Our findings highlight the limited use of asset‐based financing by Chinese SMEs. We also find that the propensity of SMEs with single‐owners to use external debt was significantly less than those with multiple owners. Furthermore, our findings suggest that single‐owned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…The results of SMEs in Egypt are quite similar to SMEs in China, as reported by a Newman et al (2013). He pointed out that a significant proportion of Chinese private SMEs is under the control of a single owner, who is typically the founder of the business.…”
Section: Descriptive Analysissupporting
confidence: 67%
See 3 more Smart Citations
“…The results of SMEs in Egypt are quite similar to SMEs in China, as reported by a Newman et al (2013). He pointed out that a significant proportion of Chinese private SMEs is under the control of a single owner, who is typically the founder of the business.…”
Section: Descriptive Analysissupporting
confidence: 67%
“…Similarly, the results of the previous SME studies revealed a higher long term ratios, ranged from 10% to 15% in Malaysia, United Kingdom, Belgium, Spain, Ireland, Netherlands, and Portugal (Shahadan and Hall et al, 2004). Finally, Egyptian SMEs showed average total leverage ratios lower than SMEs in China, which reached 54 % as reported by Newman et al (2013).…”
Section: Descriptive Analysissupporting
confidence: 56%
See 2 more Smart Citations
“…In microfinance lending, timely repayments are an incentive for repeat credit facilities although in most cases no collateral is required(Ayayi, 2012;Baklouti, 2013). The implication is that MFBs are left with nothing in case of default as the micro-entrepreneurs are not capable of bearing bankruptcy costs(Newman et al, 2013), although access to finance increases risk-bearing abilities, while choice of microfinance lending (debt) is not influenced by risk aversion. Delta had over the years witnessed considerable environmental degra-dation, social disequilibrium and poverty due to decades of ambivalent social, economic and environmental policies, and violence(Bene et al, 2011;Ogundiya, 2011;Renouard and Lado, 2012;Pegg and Zabbey, 2013).…”
mentioning
confidence: 99%